Globozoospermia - Bhattarai, L; Gautam, B; Raut, BB; Chettri, S (Kathmandu University Medical Journal, 2025)
Male infertility may be due to low sperm concentration, poor sperm motility, or abnormal morphology. Among the factors involved in male infertility, there is a rare morphology disorder called “Globozoospermia”. This condition is primarily characterized by the presence of round‐headed spermatozoa, absence of acrosomal cap and cytoskeleton defects around the nucleus. The morphological characteristics of globozoospermia are formed during spermiogenesis. We report here a case of male infertility due to morphological disorder Globozoospermia. Assessment of semen by observing macroscopic and microscopic parameters are not sufficient for sperm analysis. In present case, macroscopic and microscopic assessment was within normal range. Morphological assessment showed 80% of spermatozoa with round head and absence of acrosomal cap. The absence of acrosome makes fertilization impossible since these sperm are unable to bind to the zona pellucida. By using Intracytoplasmic Sperm Injection (ICSI), conception is possible; however, the fertilization rate remains very low.